The ant genus Tetramorium Mayr (Hymenoptera: Formicidae) in the Malagasy region—taxonomic revision of the T. kelleri and T. tortuosum species groups - Garcia, Francisco Hita; Fisher, Brian L. (Zootaxa, 2012)
The taxonomy of the T. kelleri and T. tortuosum groups is revised for the Malagasy zoogeographical region. Twenty-fourspecies are recognised of which 18 are described as new and six re-described. This raises the species richness for the genusTetramorium in the Malagasy region to 84 species. The T. kelleri group is endemic to the Malagasy region, and containsthe two species T. ankarana sp. n. and T. kelleri Forel. The T. tortuosum group is distributed in most zoogeographicalregions, but reaches its highest species richness in the Malagasy region with the 22 species treated herein. All species areendemic to the island of Madagascar. Based on morphological key characters, the group was divided into four speciescomplexes. The largest species complex is the T. andrei complex with the nine species: Tetramorium ala sp. n.,Tetramorium andohahela sp. n., Tetramorium andrei Forel, Tetramorium electrum Bolton, Tetramorium elf sp. n.,Tetramorium isectum Bolton, Tetramorium isoelectrum sp. n., Tetramorium nify sp. n., and Tetramorium voasary sp. n.The name Tetramorium robustior Forel is proposed as junior synonym of T. andrei. The most species-poor is the T. jedispecies complex with just the three species Tetramorium avaratra sp. n., Tetramorium jedi sp. n., and Tetramoriumpleganon Bolton. The T. noeli species complex holds four species: Tetramorium aherni sp. n., Tetramorium ambanizanasp. n., Tetramorium noeli sp. n., and Tetramorium singletonae sp. n. The T. smaug species complex includes the sixspecies: Tetramorium adamsi sp. n., Tetramorium marojejy sp. n., Tetramorium latreillei Forel, Tetramorium nazgul sp. n., Tetramorium sabatra sp. n., and Tetramorium smaug sp. n. Furthermore, lectotypes and paralectotypes are designated